Effects of Exergames on Brain and Cognition in Older Adults: A Review Based on a New Categorization of Combined Training Intervention - Torre, Marta Maria; Temprado, Jean-Jacques (Frontiers in Aging Neuroscience, 2022)
The literature on exergames has reported inconsistent benefits on brain and cognitive functions. Moreover, it is still unknown whether they yield to equal or superior benefits as compared to other forms of physical exercise. However, until now, a review of exergaming literature was lacking, that would reverse the “product first” approach to replacing it with a “training first” approach that is, an analysis of the different studies based on a detailed description of the type of combined training interventions that was supported by the utilized exergames. In the present review, thanks to a structured framework build around seven interacting constructs (stimuli, settings, targets, markers, outcomes, moderators, and mechanisms), which collectively afford a global picture of the determining factors of exergames training, we aimed to determine whether and under which conditions exergames could be more effective than conventional training. We concluded that, in spite of their potential to improve brain and cognition, beneficial factors contributing to exergaming efficacy as well as its underlying the mechanisms exergaming to be investigated more systematically thanks to common experimental designs based on gold standards. We proposed some directions in this respect.